Síntese quimioenzimática do levetiracetam e análogos - Amaral, Bruno Sérgio do [UNESP] (2015)
Biocatalysts (enzymes and/or microorganisms) are widely used in the synthesis of bioactive molecules, in particular pharmaceuticals, to generate or resolve chiral centers. Levetiracetam, commercially known as Keppra®, is a chiral compound with anticonvulsant properties whose pharmacological activity is related to the (S)-enantiomer. The increase in option for the use of levetiracetam over the others anticonvulsant drugs is closely associated with low incidence of side effects caused by this. Several chemosynthetic routes for its production are reported in the literature. Most of them involve numerous synthetic steps, high energy consumption, use of metal catalysts and low overall yields. On the other hand, this project aims to develop a chemoenzymatic route, with fewer steps, milder conditions and environmentally friendly reaction for the synthesis of levetiracetam and analogues (aliphatic series). The respective aromatic series was also synthesized, since it is chiral building blocks for the synthesis of compounds with known antimalarial activity. The first step was the synthesis of racemic cyanohydrin followed by substitution of the hydroxyl group by nitrogen heterocycles. Collections of nitrile hydratase enzymes type (EC 4.2.1.84) were used to catalyze the conversion of N-heterocycles α-substituted nitriles in the respective chiral amides. The enzymes were used both in isolated form (obtained commercially) as in whole cells bacteria and yeast Collection of Microorganisms of Biocatalysis Laboratory of IQ-UNESP Araraquara. The enzymatic reactions were performed in buffered aqueous medium and ionic liquid : buffer (10, 20, 40 and 80%) binary systems in order to evaluate the influence of the solvent on the enantioselectivity and yield of these reactions. The ionic liquids synthesized and used in this work were 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium...